CHROMATOGRAPHIC, RHEOLOGICAL AND CYTOCHEMISTRY EVALUATION OF “BACURI” PULP (Platonia insignis MART.) - AQUINO, ANDRÉA CARDOSO DE; LIMA, CÍCERO DE SOUZA; FEITOSA, FILIPE XAVIER; GALLÃO, MARIA IZABEL; PINTO, GUSTAVO ADOLFO SAAVEDRA; SANT'ANA, HOSIBERTO BATISTA DE (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2014)
“Bacuri” pulp was evaluated for volatile compounds, rheological behavior, and cytochemical analysis. The pulp was also submitted to physicochemical characterization. The effect of temperature on rheological behavior of whole “bacuri” pulp was investigated in this work. The rheological measurements were carried out using a Brookfield Rheometer (Model DV-II +) at shear rate range from 0.25 to 1.50 s-1 at temperatures of 30, 40, 50, 60 and 70 °C. A total of 36 compounds were detected in the headspace of the “bacuri” pulp - 34 of which were identified. The major compounds were the following: linalool, cis-linalool, trans-linalool oxide, and hotrienol, respectively. The experimental data was adjusted using a power law rheological model, with good agreement. “Bacuri” pulp shows a non-Newtonian behavior, with an apparent viscosity decreasing with increasing temperature. The “bacuri” pulp obtained activation energy at shear rate 1.50 s-1 was -14.03 kJ/mol.